2017
DOI: 10.1002/lno.10591
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variability of in situ nitrogen fixation activities associated with the Mediterranean seagrass Posidonia oceanica meadows

Abstract: This study provides the first extensive data on in situ rates of N2 fixation in minimally disturbed Posidonia oceanica meadows and their temporal and spatial variability along the Mallorcan coasts in the Mediterranean Sea. Benthic bell‐jar chambers were deployed underwater enclosing (1) natural P. oceanica shoots, (2) matted sediment of P. oceanica with the leaves carefully removed by clipping to assess the contribution of N2 fixation associated with leaves, and (3) adjacent unvegetated sediment to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
27
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 73 publications
(92 reference statements)
10
27
2
Order By: Relevance
“…Specifically, the vegetated sediments supported 3-to 4-fold higher N 2 fixation rates than bare sediments at the current summer mean SST range when expressed by area and by sediment dry weight, respectively. The N 2 fixation rates we measured in P. oceanica sediments at current summer mean SST (2.86 ± 1.26 mg N m −2 d −1 ) are higher than the rates reported in summer at similar seawater temperature by Agawin et al (2017) using benthic bell-jar chambers containing P. oceanica shoots and the underlying sediment (ranging from 0.06 to 1.51 mg N m −2 d −1 ). However, the different methodological approaches make comparisons difficult: while sediment slur- ries might slightly overestimate rates due to sediment structure disturbance and increases in organic matter availability, incubation chambers might underestimate rates due to poor diffusion of acetylene into the sediment (Welsh, 2000).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Specifically, the vegetated sediments supported 3-to 4-fold higher N 2 fixation rates than bare sediments at the current summer mean SST range when expressed by area and by sediment dry weight, respectively. The N 2 fixation rates we measured in P. oceanica sediments at current summer mean SST (2.86 ± 1.26 mg N m −2 d −1 ) are higher than the rates reported in summer at similar seawater temperature by Agawin et al (2017) using benthic bell-jar chambers containing P. oceanica shoots and the underlying sediment (ranging from 0.06 to 1.51 mg N m −2 d −1 ). However, the different methodological approaches make comparisons difficult: while sediment slur- ries might slightly overestimate rates due to sediment structure disturbance and increases in organic matter availability, incubation chambers might underestimate rates due to poor diffusion of acetylene into the sediment (Welsh, 2000).…”
Section: Discussioncontrasting
confidence: 70%
“…Nitrogen (N 2 ) fixation plays a fundamental role in balancing nutrient budgets at the basin scale in the Mediterranean Sea, with most of this N 2 fixation associated with P. oceanica seagrass meadows (Béthoux and Copin-Montégut, 1986). Indeed, endophytic nitrogen-fixing bacteria have been detected in roots of P. oceanica (Garcias-Bonet et al, 2012 and N 2 fixation has been reported in leaves and roots of P. ocean-ica (Agawin et al, 2016;Lehnen et al, 2016) and in situ incubations (Agawin et al, 2017). Therefore, the high productivity of P. oceanica in the oligotrophic Mediterranean waters is partially supported by N 2 fixation.…”
Section: N Garcias-bonet Et Al: Nitrogen Fixation In Mediterranean mentioning
confidence: 99%
“…Nevertheless, the N2 fixation rates in bare 244 sediments at current summer mean SST (1.14 ± 0.31 mg N m -2 d -1 ) are very similar to those 245 measured by benthic bell-jar in bare sediment adjacent to a P. oceanica meadow (from 0.01 to 246 1.99 mg N m -2 d -1 ) (Agawin et al, 2017), suggesting that these differences in N2 fixation rates in 247 P. oceanica sediment might also be due to variability among sites. The N2 fixation rates in C. (25 and 27 o C) could account for 6.7 to 7 %, 11.5 to 13.8 % and 1.1 to 1.8 % of the 267 nitrogen requirements for P. oceanica, C. nodosa, and C. prolifera, respectively.…”
Section: Discussion 226supporting
confidence: 52%
“…Warming enhances 64 sediment sulfate reduction rates (Robador et al, 2016), leading to an increase in sulfide 65 (Koch et al, 2007). In the Mediterranean Sea, heatwaves and warming trigger sulfide 67 intrusion in P. oceanica shoots (García et al, 2013), which has toxic effects on plant meristems 68 2016; Lehnen et al, 2016) and in situ incubations (Agawin et al, 2017). Therefore, the high 81 productivity of P. oceanica in the oligotrophic Mediterranean waters is partially supported by N2 82 fixation.…”
Section: Introduction 43mentioning
confidence: 99%
“…The overall composition of sedimentary pigments from the mat cores was consistent with the expected assemblage of primary producers observed in P. oceanica meadows. In general, modern macroalgal species are characteristically composed mainly of calcareous Rhodophyta and non-calcified Ochrophyta, whereas microalgal epiphytes usually include diatoms, dinoflagellates and cyanobacteria in declining relative abundance (Piazzi et al, 2016;Agawin et al, 2017). Similarly, the modern phytoplankton assemblages are mainly composed of diatoms and dinoflagellates (Moncer et al, 2017), while the water column near Cabrera is known to harbour a great abundance of pico and nanoplankton, dinoflagellates, coccolitophorids and diatoms (Vives, 1993).…”
Section: Seagrass Phototrophic Communitymentioning
confidence: 99%